The Effect of Homophily and Expertise on Purchase Intention Luxury Cars on Youtube Platform Users - Pribadi, Andre Dwithama (RSF Conference Series: Business, Management and Social Sciences, 2023)
Social Media influencer is one of the primary keys in the advertising industry, which provides more impetus to increase consumers’ sense of homophily towards brands. This is assisted by the level of expertise possessed by SMI, which is in accordance with the brand identity and elements owned by the brand. The level of homophily and expertise can increase image satisfaction and advertising trust in building a sense of emotional connection and shared values between consumers and brands. This interpersonal feeling can be interpreted as a self-brand connection where consumers with a high sense of connection will increase the consumer’s desire to buy and feel the benefits provided by product consumption emotionally or practically. This research focuses on the luxury car industry, which is often promoted through social media influencers on the YouTube platform. The use of the YouTube platform has the right features to provide information through audio, visuals, and also the right duration in promoting luxury cars. Respondents who were targeted using non-probability sampling also had specific criteria where Respondents were Youtube users who had watched automotive YouTuber content and recognized SMI luxury cars on Youtube.